Body image among female breast cancer survivors in Selangor and Kuala Lumpur and its associated factors - Chin, Yi Ching
The purpose of this cross-sectional study was to determine the associations between socio-demographic factors, psychological factors, body weight status and dietary intake with body image among female breast cancer survivors in Selangor and Kuala Lumpur. It was carried out at the National Cancer Society of Malaysia (NCSM) and the Breast Cancer Welfare Association (BCWA). A total of 59 female breast cancer survivors with a mean age of 58.44 years (SD = 8.39) participated in this study. The respondents completed a self-administered questionnaire on socio-demographic backgrounds, psychological characteristics (depression and anxiety) and body image. Weight and height of the respondents were measured using appropriate instruments and dietary intake was assessed using a two-day 24-hour dietary recall. Majority of the respondents were Chinese (52.5%), followed by Malay (23.7%), Indian (15.3%) and others (8.5%). The mean number of year after diagnosis of the respondents was 9.74 years (SD = 6.69). About half of them (53.4%) underwent mastectomy surgery without reconstruction. Most of the respondents (83.1%) had no family history of breast cancer. The mean BMI of the respondents was 23.45 kg/m² (SD= 3.24 kg/m²), with one fourth of them (25.5%) was classified as overweight and obese. The prevalence of anxiety and depression for this study were 25.4% and 6.8% respectively. In term of diet, majority of the respondents (96.6%) did not achieve the recommended energy intake. None of the respondents achieved the recommended fiber intake per day. For body image, the mean score was 18.93 (SD = 12.50), indicating that the respondents had low body image disturbance. Pearson Productmoment Correlation analysis found that respondents' age (r=-0.373, p = 0.004) and number of years after diagnosis (r = -0.309, p =0.018) were significantly correlated with body image disturbance. Significant correlations were also found between anxiety (r=0.436, p= 0.001) and depression (r=0.303 , p=0.019) with body image disturbance. No association was found between body weight status and dietary intake with body image disturbance. In conclusion. although most of the survivors in this study reported low body image disturbance, correlation analysis revealed that younger age of women, lesser years after diagnosis, anxiety and depression were associated with greater body image disturbance. Therefore, nutrition intervention should focus on young survivors as well as those who are newly diagnosed, and tackle both the psychological and body image issues to reduce their body image disturbance.